2008
DOI: 10.3746/jkfn.2008.37.4.437
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ginseng and Herbal Plant Mixtures on Anti-Obesity in Obese SD Rat Induced by High Fat Diet

Abstract: Anti-obesity effects of ginseng and herbal plant mixtures were investigated to develop natural materials for anti-obesity. After inducing obesity with high fat diet for 8 weeks in male SD rats, ginseng and herbal plant mixtures DM1 (ginseng, puer tea, opuntia) and DM2 (ginseng, puer tea) were administrated orally to rats for another 8 weeks. During administration, food efficacy ratio and body weight of rat were measured twice weekly. After administration, body weight, body fat contents, and serum lipid level w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 15 publications
1
3
0
1
Order By: Relevance
“…These result are similar to a reports that obese rats induced high fat diet takes in food at lower degree than a normal group, but the FER was higher [37,49], and which is reported to stem from the high calories by high fat [37]. Rats are considered obese when T.M.…”
Section: Resultssupporting
confidence: 80%
“…These result are similar to a reports that obese rats induced high fat diet takes in food at lower degree than a normal group, but the FER was higher [37,49], and which is reported to stem from the high calories by high fat [37]. Rats are considered obese when T.M.…”
Section: Resultssupporting
confidence: 80%
“…천연물을 활용한 항비만 소재 개발에 관한 결과를 살펴보면 작용기전에 따라 지방의 소화 및 흡수를 저해하는 물질로서 키토산, 플라보노이드 등이 있으며 [56], 열 발생을 유도하여 지방 축적을 억제하는 물질로서 고추의 캡사이신, 녹차의 카 테친, 레티노익산 등이 있다 [18]. 그리고 지질대사를 조절하는 카르니틴이 있으며, 생약재로는 지실, 결명자, 소나무잎, 천궁 등이 체중조절에 효과가 있다는 결과가 보고되었다 [36].…”
Section: 서 론unclassified
“…This showed antiinflammatory and antisteatotic effects in the NASH model. Recently, various studies have been striving to develop a complex treatment by mixing ingredients known to have disease-relieving effects [ [15] , [16] , [17] , [18] ]. These attempts may address the limited supply of existing ingredients and lead to the development of new health functional foods.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have suggested that a mixture of KRG and other botanical therapeutic ingredients such as coffee, puer tea, buckwheat or licorice ( Glycyrrhiza uralensis Fischer) have complex enhancement effects on various indices related to antioxidative, antibacterial, antiobesity, or collagenase inhibitory activity [ [15] , [16] , [17] , [18] ]. Among them, glycyrrhizin, a constituent of licorice, has a sweet taste and is known to have antiobesity effects and to alleviate allergy asthma [ 17 , 19 ].…”
Section: Introductionmentioning
confidence: 99%